KAJIAN PENGGUNAAN TRAS LOMPOTOO SEBAGAI AGREGAT HALUS PADA LAPIS PONDASI BAWAH DITINJAU DARI SPESIFIKASI UMUM, 2007 DAN 2010 - Achmad, Fadly; Maksud, Riskiyanto (FSTPT Indonesia, 2015)
Gorontalo Province has several material sources which are used as embankment material or base course. These materials have been exploited in large numbers each year to fulfill the infrastructure needs especially the highway. The large numbers of needs causes the decrease of material deposits in Gorontalo province. If there is not any effort to look for the alternative material sources, it is feared, in the future, this region will bring the materials from other areas which of course will need a quite high costs. Over the years, the taking material only focuses in Pilolalenga, Alopohu, Molintogupo, Botumoito, Randangan, Bumela and Bone River, while many other locations have the potential to serve as alternative sources of highway materials. Besides the huge number of materials need, the problem that commonly faced in several districts of Gorontalo province is the use of material specification. For example, some districts are still use the general specification 2007 as the reference, while the general specification 2010 has existed. The research used Tras Lompotoo as fine aggregate and gravels which were taken from Bone River as coarse aggregate. The method of research was experiment research. The tests included water content, gradation, Atterberg limits, abration, compaction, and CBR. The research result showed that the gradation composition that fulfilled the general specification was 30% of Tras Lompotoo : 70% of Bone Gravels. CBR unsoaked value was 70%, CBR soaked was 27%, while γd max = 2,07 gr/cm3 and wopt =6,00%. The comparison only gave properties value in general specifications 2007.